Use of Morphine Sulphate by South African Paramedics for Prehospital Pain Management - Craig Vincent-Lambert; Joalda Marthiné de Kock (Pain Research and Management)
BACKGROUND: Evidence in the literature highlights the fact that acute pain in the prehospital setting remains poorly managed. Morphine remains the most commonly used analgesic agent in the South African prehospital emergency care setting. Although guidelines and protocols relating to the dosage and administration of morphine exist, little data are available describing its use by South African paramedics.